Black Women Family Childcare Providers’ Roles as Community Mothers During the Covid-19 Pandemic - (:unkn) unknown (My University, 2020)
BLACK WOMEN FAMILY CHILDCARE PROVIDERS’ ROLES ASCOMMUNITY MOTHERS DURING THE COVID-19 PANDEMIC Black women family childcare providers have withstood and adapted to numerous socioeconomic and political challenges and have remained a source of stability and connection within the Black community. This study is situated in the midst of the social disruption resulting from a pandemic that deeply impacted the landscape of early care and education. The purpose of this study was twofold: first, to describe the cultural knowledge of Black women early childhood educators as they reacted and organized to support young learners and their families in conditions of hardship, and second, to identify the types of capital with which the women engaged as they navigated their role in an essential profession. To honor the voices of The Storytellers (i.e., Black women family childcare providers) and illuminate their unique perspectives, the author used methods rooted in my endarkened feminist narrative and Black feminist thought frameworks. The stories gathered through this sacred and rigorous work showed that the cultural knowledge of The Storytellers was rooted in (a) their spirituality and deep faith in God; (b) their boss mentality and willingness to act as autonomous agents within their businesses and communities; (c) their drive to educate and empower the next generation of women; and (d) an understanding that their roles as community mothers stretches far beyond the reach of their childcare businesses. Endarkened feminist narrative is discussed as a qualitative research approach which marries the praxis of narrative inquiry with the sacred storytelling tradition and spiritual transmission that is foundational to Afrocentric cultural heritage. The practice of EFN, which recognizes research as a spiritual act, draws from Dillard’s (2016) endarkened feminist epistemological (EFE) process of (re)membering, Yosso’s (2005) description of cultural capital, and Tillman’s (2002) description of culturally relevant research. Implications are provided for state governing agencies and for the field of early childcare as a whole. First, on the state level, the author urges policymakers and legislators to reconceptualize how family childcare providers are assessed by policymakers, QRIS programs, and other regulatory agencies. In this, the author advocates for a more culturally responsive community-based rating system that champions the voices and values of parents, families, and other community-sanctioned vehicles for the definition of quality in early childhood education. Second, policymakers should examine the structures in place to support and protect those who care for our youngest citizens. Finally, for the field of early education, the author encourages a critical review of the way the cultural knowledge of Black women early childhood educators is represented in education reform and policy. Within the final reflections of this work, the author finds truths about her heritage that help her see herself more clearly as a Black woman early childhood educator.
Keywords: Black Women; COVID-19; Cultural Capital; Cultural Knowledge; Early Childhood Education; Educating Black Children